Evaluation of antiretroviral therapy effect and prognosis between HIV-1 recent and long-term infection based on a rapid recent infection testing algorithm - Zhao, Jianhui; Chen, Hongjie; Wan, Zhengwei; Yu, Tao; Liu, Quanxun; Shui, Jingwei; Wang, Haiying; Peng, Jie; Tang, Shixing (Frontiers in Microbiology, 2022)
Early diagnosis of HIV-1 infection and immediate initiation of combination antiretroviral therapy (cART) are important for achieving better virological suppression and quicker immune reconstitution. However, no serological HIV-1 recency testing assay has been approved for clinical use, and the real-world clinical outcomes remain to be explored for the subjects with HIV-1 recent infection (RI) or long-term infection (LI) when antiretroviral therapy is initiated. In this study, a HIV-1 rapid recent-infection testing strip (RRITS) was developed and incorporated into the recent infection testing algorithms to distinguish HIV-1 RI and LI and to assess their clinical outcomes including virological response, the recovery of CD4+ T-cell count and CD4/CD8 ratio and the probability of survival. We found that the concordance between our RRITS and the commercially available LAg-Avidity EIA was 97.13% and 90.63% when detecting the longitudinal and cross-sectional HIV-1 positive samples, respectively. Among the 200 HIV-1 patients analyzed, 77.5% (155/200) of them were chronically infected and 30% (60/200) of them were AIDS patients. After cART, 4.1% (5/155) of the LI patients showed virological rebound, but none in the RI group. The proportion of CD4+ T-cell count > 500 cells/mm3 was significantly higher in RI patients than in LI after 2 years of cART with a hazard ratio (HR) of 2.6 (95% CI: 1.9, 3.6, P < 0.0001) while the probability of CD4/CD8 = 1 was higher in RI than in LI group with a HR of 3.6 (95% CI: 2.2, 5.7, P < 0.0001). Furthermore, the immunological recovery speed was 16 cells/mm3/month for CD4+ and 0.043/month for the ratio of CD4/CD8 in the RI group, and was bigger in the RI group than in the LI patients (P < 0.05) during the 1st year of cART. The survival probability for LI patients was significantly lower than that for RI patients (P < 0.001). Our results indicated that RRITS combined with RITAs could successfully distinguish HIV-1 RI and LI patients whose clinical outcomes were significantly different after cART. The rapid HIV-1 recency test provides a feasible assay for diagnosing HIV-1 recent infection and a useful tool for predicting the outcomes of HIV-1 patients.